Steel design and reliability using Eurocode 3 - Byfield, Michael Patrick (1996)
The twin aims of this research were to improve the presentation of codified design information and to investigate the methods used to calibrate the partial safety factors applied to resistance functions (ΎR-factors) so as to improve both the economy and the reliability of the predictions.